(3eUWdM GdETGQGJ aj GdbQGAGJ GdSHYI GdRhGFO Yf GdKbGJs - (3Ydj Hf YKeGf Hf eMeO Hf CMeO, CHh GdHbGA GHf GdYPOj, hjYQa HGHf GdbGUMs
(3ChdgG (B:s
(3bGd eDdag GHf GdaGUM GdYPQi QMeg Gddg GdMeO ddg GdPi LYd GdbQBf dCgdg TQakG hfhQkG CeG HYO aEfi deG aQZJ ef GdbQGAI HeG JVefg cJGH GdYfhGf s
(3BNQgG (B:s
(3hjScJ Ydi BNQ GdShQI Ke jcHQ hjSei ehUhdkG HChd GdShQI aEPG NJe bhd GdMeO hNeS BjGJ ef Chd GdbQBf Edi bhdg JYGdi GdeadMhf gPG BNQ GdcJGH s
(3GdChQGb GdChdi HNW MOjKs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs